Preparation of Development of the Assessment System of Quality of Wine and Wine Products - Seifulla, Dadashova Kamala; Aliev, Ilkin Emil (Acta Universitatis Danubius. Œconomica, 2024)
Viticulture and winemaking are socially important and highly profitable sectors of the agro-industrial complex of the Republic of Azerbaijan. Both of these areas have significant potential for future dynamic development. At the same time, there are a number of risks and dangers in these areas. The most important of these risks and hazards is the impact of adverse natural phenomena on grape production. Such phenomena can be explained by climate change, as well as the production and commercialization of counterfeit wine products. Currently, in conditions of intense competition, the market share of wine products that do not fully comply with current legislation, norms and requirements leads to a constant increase, which confuses consumers. At the same time, the level of threats to the health, property and life of the population increases. As a result, public confidence in the industry's products is declining. In addition to administrative measures used to effectively prevent or minimize unfair competition at the stage of circulation and production. It is necessary to expand the practical capabilities of objective analytical and expert identification of wine products, to increase the criteria for the reliability of wine products and the assessment of their quality systems. An effective way to achieve this goal is to evaluate specific properties (components) of wine products that remain unchanged throughout the entire production chain of turning grapes into wine or the processing of which is technologically complex, based on modern scientific knowledge, which is accordingly economically feasible. To solve the problem of a comprehensive study of the specific properties of wine products, it is necessary to develop and use new techniques, including both analytical and expert methods for studying the component composition, capable of ensuring the reliability and objectivity of the results obtained. This will ultimately provide the necessary level of control over compliance with laws and regulations, and will also make it possible to carry out identification by identifying inaccurate information about the product, for example, its type, name and place of origin (region). The objectivity and reliability of the results obtained on the basis of new methods must be ensured by the maximum possible volume of scientifically based and confirmed information on qualitative and quantitative changes in the prices of the analyzed indicators. Thus, the development and implementation of a quality assessment system, including the authenticity of wine products, based on fundamental scientific knowledge and modern research tools, are urgent tasks for scientific and expert support of production, circulation and import substitution in accordance with the law.